2018
DOI: 10.4172/2090-7214.1000284
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of HIV Positive Breastfeeding Mothers in Prevention of Mother to Child Transmission of HIV in Ouagadougou (Burkina Faso) and Associated Factors

Abstract: World Health Organization (WHO) places strong emphasis on exclusive breastfeeding of HIV exposed infants during the first 6 months, combined to antiretroviral treatment for mothers and prophylaxis for infants. However, adherence to safe breastfeeding among HIV infected mothers is still a major challenge in Burkina Faso. We conducted a cross sectional study in four hospitals in Ouagadougou, Burkina Faso in order to explore knowledge, attitudes and practices of HIV infected breastfeeding mothers attending select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
2
5
1
Order By: Relevance
“…The proportion of participants who indicated awareness of the possibility of mother-to-infant HIV transmission during breastfeeding was similar to the figure reported from Enugu (39.0%; Anoje et al, 2012), but lower than that from Ibadan (86%), both in Nigeria (Balogun & Owoaje, 2015). In sub-Saharan Africa, our figure is comparable with reports from Ethiopia (31.4%; Tesfaye et al, 2015), but much lower than those from Burkina Faso (99.5%; Yonaba et al, 2018), Kenya (85.5%; Wachira et al, 2009), and South Africa (78%; Ladzani et al, 2011). When making these comparisons, there is need for caution due to variations in study populations, design, measurements, and the timing of the studies.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The proportion of participants who indicated awareness of the possibility of mother-to-infant HIV transmission during breastfeeding was similar to the figure reported from Enugu (39.0%; Anoje et al, 2012), but lower than that from Ibadan (86%), both in Nigeria (Balogun & Owoaje, 2015). In sub-Saharan Africa, our figure is comparable with reports from Ethiopia (31.4%; Tesfaye et al, 2015), but much lower than those from Burkina Faso (99.5%; Yonaba et al, 2018), Kenya (85.5%; Wachira et al, 2009), and South Africa (78%; Ladzani et al, 2011). When making these comparisons, there is need for caution due to variations in study populations, design, measurements, and the timing of the studies.…”
Section: Discussionsupporting
confidence: 71%
“…Compared to mothers in the current study, fewer than half (48.1%) of mothers in the Burkina Faso study considered antiretroviral therapy to be protective (Yonaba et al, 2018). Further, a larger proportion of respondents in the current study indicated awareness of the increased risk of HIV transmission with mastitis compared to their counterparts in Burkina Faso (26%; Yonaba et al, 2018). Further, the proportion of study respondents that mentioned oral ulcers in infants as facilitators of HIV acquisition was much higher than among their contemporaries in Zimbabwe (3.6%; Piwoz et al, 2005).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations